Speed Control Of Permanent Magnet Brushless DC Motor - Chan, Hao Jie (Universiti Sains Malaysia, 2017)
Permanent Magnet Brushless DC motor (PM BLDC) is very popular in many industrial applications because of its good dynamic response, long operating life, high efficiency and wide speed range. This project aims to develop and implement a closed-loop control system to achieve PM BLDC motor speed control and to show good dynamic response. The closed-loop control system is first designed and then implemented inside a dsPIC30F2010 Digital Signal Processor on a Microchip PICDEM MCLV Development Board. The motor is a six-poles, three-phase PM BLDC motor. The system is tested with three different speed references and changing speed references to evaluate the motor performance and response. The results show that there is a 6.7% overshoot when the motor is controlled to run from zero to 1000 rpm, and no overshoot is observed for 2000 rpm and 3000 rpm. The response also shows that the speed control gives good result even if the speed reference is changed during motor operation. The closed-loop speed control system gives satisfactory result even when the motor is connected to a fan load.